2019
DOI: 10.1016/j.ebiom.2019.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid 2-hydroxylation inhibits tumor growth and increases sensitivity to cisplatin in gastric cancer

Abstract: Background Most gastric cancers are diagnosed at an advanced or metastatic stage with poor prognosis and survival rate. Fatty acid 2-hydroxylase (FA2H) with high expression in stomach generates chiral ( R )-2-hydroxy FAs (( R )-2-OHFAs) and regulates glucose utilization which is important for cell proliferation and invasiveness. We hypothesized that FA2H impacts gastric tumor growth and could represent a novel target to improve gastric cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 50 publications
8
78
0
Order By: Relevance
“…The survival rate of AGS cells varied depending on the expression levels of TC2N; TC2N knockdown significantly decreased the cell survival rate, reflecting a higher sensitivity of AGS cells to DPP, paclitaxel and 5-FU when TC2N expression was inhibited. Acquired drug resistance is one of the predominant reasons for the low cure rate and high recurrence rate in patients with gastric cancer, especially at an advanced stage ( 23 ). Thus, improving the sensitivity of cancer cells to chemotherapeutics may be an important strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate of AGS cells varied depending on the expression levels of TC2N; TC2N knockdown significantly decreased the cell survival rate, reflecting a higher sensitivity of AGS cells to DPP, paclitaxel and 5-FU when TC2N expression was inhibited. Acquired drug resistance is one of the predominant reasons for the low cure rate and high recurrence rate in patients with gastric cancer, especially at an advanced stage ( 23 ). Thus, improving the sensitivity of cancer cells to chemotherapeutics may be an important strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our results strongly argue that a combination of FA2H and UGT8 expression drives the synthesis of 2-hydroxyHexCer, the exact mechanism accounting for the accumulation of these metabolites specifically in adenocarcinomas, which should be confirmed by ulterior investigations of sulfatides and gangliosides, which were also linked with cancer metastasis (35,36) and multi-drug resistance (37). Aligning with the theory that complex metabolic alterations, rather than single molecule levels, should be taken into account for delineating mechanisms of disease, low FA2H was associated with tumor growth and patient survival in gastric tumors (38), but UGT8 is not overexpressed in gastric tumors in Fig. 2.…”
Section: Discussionmentioning
confidence: 88%
“…FA2H downregulation has been observed in triple negative breast cancer tissues and cell lines (27). FA2H expression levels were lower in gastric tumor tissues compared with healthy control tissues (26). Moreover, another study revealed that FA2H levels were higher in adenocarcinoma compared with squamous and neuroendocrine carcinoma (28).…”
Section: Microrna-1297 Downregulation Inhibits Breast Cancer Cell Epimentioning
confidence: 98%
“…As a hydroxy fatty acid enzyme, fatty acid 2-hydroxylase (FA2H) promotes 2-hydroxylation of fatty acid N-acyl chain (23). It has been reported that 2-hydroxyceramide and FA2H, which are expressed in several tissues (24,25), participate in multiple cell signaling pathways, such as the AMPK and mTOR/p70 ribosomal protein S6 kinase 1 (S6K1)/glioma-associated oncogene homolog 1 pathways (26). FA2H also serves a crucial role in the occurrence and development of tumors (26).…”
Section: Microrna-1297 Downregulation Inhibits Breast Cancer Cell Epimentioning
confidence: 99%
See 1 more Smart Citation